From cure to crisis: Rifampicin-induced thrombocytopenia in spinal tuberculosis - Malapati, Sai Nikhitha; Malapati, Sai Geethika; Muktinootalapati , Shyam Sunder (Indian Journal of Case Reports, 2025)
Thrombocytopenia, a rare adverse reaction of rifampicin, requires prompt detection and management. We report the case of a 16-year-old female with spinal tuberculosis who developed thrombocytopenia after temporarily discontinuing antitubercular treatment. Upon stopping the treatment after admission, her platelet counts normalized. However, re-administration of rifampicin alone led to a recurrence of thrombocytopenia within 1 day, confirming rifampicin-induced thrombocytopenia. The patient fully recovered after discontinuing rifampicin and tolerated a modified regimen of isoniazid, ethambutol, pyrazinamide, and levofloxacin. This case highlights the need to monitor platelet count in patients receiving rifampicin.